Development of chloride-free electrolyte for rechargeable magnesium battery - Horia, Raymond (Nanyang Technological University, 2022)
A primary challenge in developing rechargeable magnesium battery electrolytes is to create a chloride-free electrolyte with a facile fabrication process. The chloride-based additive is generally added to conventional magnesium electrolytes to improve their compatibility with the magnesium anode. The additive, however, tends to induce corrosion on the current collector of the cathode. This side effect increases the parasitic reaction and cell degradation rate during the battery operation. Although several novel magnesium electrolytes have been reported to be compatible with the magnesium anode, even in a chloride-free electrolyte formulation, the mass scale production viability of these electrolytes is low. To create a chloride-free simple to produce electrolyte formulation, the thesis seeks to explore various combinations of commercially available magnesium salts, additives, and solvents. The report shows that by using the appropriate combination of non-passivating magnesium salt, moisture scavenging additive, and ether-based solvent, a chloride-free electrolyte with good compatibility with the magnesium metal anode can be created. The electrolyte was also found to have high anodic stability on stainless steel and was also found to be compatible with the copper sulfide cathode material at high temperature.